2023
DOI: 10.21037/hbsn-22-442
|View full text |Cite
|
Sign up to set email alerts
|

Adipose tissue induces a better liver regeneration after living liver donation in normal weight donors

Abstract: Background: Extrahepatic body fat could be a relevant factor affecting liver regeneration after partial hepatectomy. The aim of this study was to evaluate the potential role of body fatty tissue in liver regeneration capacity after liver resection in a cohort of living donors. Methods:We observed liver regeneration in 120 patients: 70 living donors who underwent right hepatectomy and 50 recipients who got a right graft transplantation. Liver volumetry and body fat analysis were performed based on the computed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 18 publications
0
1
0
Order By: Relevance
“…These results correspond with recent work from our group, which investigated liver regeneration in normal-weight living donors and found that adipose tissue induces better liver regeneration after living donation. [33] The presence of malignancy as an indication for liver transplantation was a significant independent variable negatively influencing the liver volume gain in our cohort. To our knowledge, this finding has not yet been described and requires further research.…”
Section: Discussionmentioning
confidence: 71%
“…These results correspond with recent work from our group, which investigated liver regeneration in normal-weight living donors and found that adipose tissue induces better liver regeneration after living donation. [33] The presence of malignancy as an indication for liver transplantation was a significant independent variable negatively influencing the liver volume gain in our cohort. To our knowledge, this finding has not yet been described and requires further research.…”
Section: Discussionmentioning
confidence: 71%